A history of horror - Dixon, Wheeler W., 1950- (Rutgers University Press, 2010)
Ever since horror leapt from popular fiction to the silver screen in the late 1890s, viewers have experienced fear and pleasure in exquisite combination. A History of Horror, with rare stills from classic films, is the only book to offer a comprehensive survey of this ever-popular film genre. Chronologically examining over fifty horror films from key periods, this one-stop sourcebook unearths the historical origins of legendary characters and explores how the genre fits into the Hollywood studio system and how its enormous success in American and European culture expanded globally over time.-- Provided by publisher.
Keywords: Horror films -- History and criticism.; Films d'horreur -- Histoire et critique.; ART -- Film & Video.; PERFORMING ARTS -- Film & Video -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Horror films; Criticism, interpretation, etc.